PERAN FINANCIAL TECHNOLOGY SEBAGAI MEDIATOR PADA PENGARUH LITERASI KEUANGAN TERHADAP KINERJA UMKM - Alvina Damayanti; Mardiana (AKUNTANSI DEWANTARA, 2023)
This study intends to evaluate and examine the impact of financial literacy on MSME performance dwith financial technology as a mediating variable. As many as 83 respondents from UMKM in Gianyar Regency in 2023 became the sample for this study, which used quantitative research techniques. According to the study findings, financial literacy has a significant and beneficial impact on MSME performance. MSME performance is positively and significantly influenced by financial technology . MSME performance is positively and significantly influenced by financial literacy. And financial technology is unable to mediate the impact of lfinancial iteration to MSME performance.